An Analysis of The Second Year Students’ Ability in Writing a Narrative Text in English Department of Universitas Negeri Padang - Alfintan Rahmadini Putri; Muhammad Al Hafizh (Universitas Negeri Padang, 2020)
The purpose of this study was to determine the level of student ability in writing narrative text as seen from the generic structure of the text. The population of this study was all students in the second semester of the 2019-2020 academic years majoring in English education at Universitas Negeri Padang. The study population consisted of 169 students from 5 classes, namely: K1, K2, K2, K4, and K5. Sampling using a random sampling technique then obtained a sample of 42 people. The instrument used was an online writing test via a Google form. Students' writing was analyzed using an assessment rubric in accordance with this research. The results showed that the students' ability in writing the narrative text was in the medium category.